2018
DOI: 10.1177/2325967118759631
|View full text |Cite
|
Sign up to set email alerts
|

Does the Lever Sign Test Have Added Value for Diagnosing Anterior Cruciate Ligament Ruptures?

Abstract: Background:Diagnosing an anterior cruciate ligament (ACL) rupture based on a physical examination remains a challenge for both surgeons and physical therapists. The lever sign test was developed to overcome the practical limitations of other tests and to optimize diagnosis. An evaluation of the measurement properties of the lever sign test is needed to make adequate interpretations in practice.Purpose:To evaluate the reliability and diagnostic value of the lever sign test.Study Design:Cohort study (diagnosis);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
12

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 20 publications
1
63
0
12
Order By: Relevance
“…3,11 Lichtenburg et al found the sensitivity and specificity for the lever sign test to be 39% and 100%, respectively. 12 They found the values for the Lachman test to be 87% and 91%, respectively. While Lichtenburg et al also found that the sensitivity of the lever sign test was significantly lower than the Lachman test, it contradicts the other two studies by showing the specificity of the lever sign to be better than the Lachman test.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 97%
See 4 more Smart Citations
“…3,11 Lichtenburg et al found the sensitivity and specificity for the lever sign test to be 39% and 100%, respectively. 12 They found the values for the Lachman test to be 87% and 91%, respectively. While Lichtenburg et al also found that the sensitivity of the lever sign test was significantly lower than the Lachman test, it contradicts the other two studies by showing the specificity of the lever sign to be better than the Lachman test.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 97%
“…11 Lichtenburg et al compared tests to arthroscopic visualization. 12 Mulligan et al found the sensitivity and specificity values for the lever sign to be 33% and 50%, respectively. In comparison, the Lachman test had values of 65% and 100%, respectively.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations